Trust in health system during COVID-19 and student value system in Southeast Europe - Pavlović Vinogradac, Valentina (Sociološki pregled, 2020)
The COVID-19 pandemic caused by the SARS-CoV-2 virus has affected the entire world. In order for the country to function under normal conditions, it is important that there is trust in state institutions. Trust in institutions is therefore particularly important in crisis situations, and trust in the health system during a pandemic is crucial. The aim of this paper is to investigate the extent to which the value system of young people in the three countries of Southeast Europe – Bosnia and Herzegovina, Croatia and Serbia is related to young people’s trust in the health system in each of these countries during the COVID-19 pandemic. The research was conducted on a total of 1024 students by the survey method. Shalom Schwartz’s model of basic human values was used as a starting point for the research. The paper analyzes the factors of the value system (self-transcendence, openness to change, conservation, self-enhancement) in trust in health system by linear regression. The results showed that the value of conservation was a significant predictor of trust in the health system in all three surveyed states.
Keywords: trust in health system; values; COVID-19; Croatia; Bosnia and Herzegovina; Serbia